The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.21638/11701/spbu08.2018.301
|View full text |Cite
|
Sign up to set email alerts
|

Organizational and Psychological Aspects of Human Resource Management in Agile Companies

Abstract: Agile-подход к управлению человеческими ресурсами (УЧР) является принципиально новым, недостаточно изученным направлением в практике менеджмента, о чем свидетельствует небольшое количество работ по данной проблематике в научной и бизнес-литературе. В статье отражены результаты исследования проблем управления человеческими ресурсами в двух ИТ-компаниях, внедряющих этот подход в управление проектами. В процессе исследования с представителями компаний были проведены глубинные интервью, которые базировались на AMO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…The study used the opportunity-enhancing HRM practices of the HRM questionnaire developed by Zavyalova et al (2018). These practices are referred to as Empowerment-enhancing HR practices by Gardner et al (2011).…”
Section: Human Resource Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study used the opportunity-enhancing HRM practices of the HRM questionnaire developed by Zavyalova et al (2018). These practices are referred to as Empowerment-enhancing HR practices by Gardner et al (2011).…”
Section: Human Resource Practicesmentioning
confidence: 99%
“…Zavyalova et al (2018) demonstrated that agile firms tend to more strongly rely on HRM practices (especially, motivation-and opportunity-enhancing) in ensuring high organizational performance. Furthermore, successful agile firms had more centralized HRM architectures with less authority diffusion among different levels of management.…”
mentioning
confidence: 99%